The Intermittency of Masquerading Rituals as a Marker of Political Change. - KEZICH, GIOVANNI; MOTT, ANTONELLA (Folklore (14060957), 2025)
Traditional masquerading at carnival time and similar traditional occasions speaks the language of unbroken continuity through time and is generally perceived as a straight line from time immemorial to the present day. At closer quarters, however, it becomes apparent that most, if not all, masquerading traditions are marked by a considerable intermittency with frequent interruptions often lasting whole decades. A comparative outlook at a few masquerades, largely from Italy, will show this intermittency as a precise response to the ongoing stimuli of the larger political context.